Influence Style Leadership, Motivation and Discipline Work to Performance Employee - Agus Rohmat Hidayat; Oxy Prabowo; Septien Dwi Savandha (Syntax Idea)
The aim of this research is to determine the effect leadership style, motivation and work discipline towards performance employee. Method study this use descriptive analysis with a correlation approach. T test results It is obtained that the calculated t value of the motivation variable (X2) has mark p-value as big as 0,000 <0.05 It means significant, while the t count is 7.287 > from the t table 1.987, meaning it is significant. Matter the means 7,287 (X2) motivation in a way Partial influential to Performance Employee (Y). The size influence motivation to Performance employee is as big as 37.6%. 3) There is influence discipline to Employee performance. The results of the t test showed that the t value was calculated variable motivation (X3) own mark p-value as big as 0,000<0.05 means significant, while the t count is 4.794 > from the t table 1,987 It means significant. Matter the means 4,794 (X3) discipline in a way Partial influential to Performance Employee (Y). The size influence discipline to Performance employee is as big as 20.7%. 4) There is influence which significant between Style Leadership (X 1), Motivation (X2) and discipline (X3) to Performance Employees (Y) is 0.739, this shows that these four variables have an influence the strong one is at the limit interpretation intermediate R value 0.60 – 0.799.